Comparison of combustion properties of simulated biogas and methane (2009)
ABSTRACT: The utilization of new renewable energy sources has been of special interest during the past years, seeking to decrease our dependence on fossil fuels and the corresponding environmental impact derived from their use. The combustion properties of a simulated gas composed of 60% methane and 40% carbon dioxide in volume are determined in this paper by means of calculation algorithms developed by the GASURE team, comparing them to pure methane properties. Furthermore, the effect of these properties on premixed flame characteristic phenomena is demonstrated. These properties were determined by theoretical estimations. The characteristic phenomena (laminar deflagration velocity, flame structure, radiation pattern) are determined experimentally. Results show a high effect of carbon dioxide in the combustion properties and characteristic parameters of a biogas premixed flame such as laminar deflagration velocity, flame structure and gas-methane exchangeability problems. The difference regarding flame structure and combustion properties lead to a difference in radiation pattern of the gases studied.